Frequency of pathogens in neonatal meningitis in Lima, Perú, between 2001 and 2021 - Minei-Ogata, Mariana S. (2023)
Objective: To describe the most frequent pathogenic agents identified in neonatal meningitis in Peru. Material and methods: Descriptive, comparative, cross-sectional study based on data bases from PubMed and SciELO, using the key words “Neonatal”, “Meningitis” and “Perú”, and from virtual repositories of medical schools in Peru, with the key words “Neonatal” and “Meningitis”, between 2001 and 2021. Two independent reviewers assessed the articles’ titles and abstracts to be included. Results: 477 articles were found from which only 5 were included; 2 studies were excluded due to lack of descriptive identification of the microorganisms, so that only 3 studies were finally selected.Conclusions: The most frequently found microorganisms were Listeria monocytogenes, coagulada-negative. Staphylococcus and Escherichia coli, predominantly grampositive bacterias. The viral etiology was uncommon, and all cases had a late onset. There was only 1 case due to Candida albicans. An epidemiologic monitoring of neonatal meningitis is not established in Peru.